2018
DOI: 10.20448/journal.522.2019.51.56.62
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Academic Self Efficacy of University Students in the Sports Area

Abstract: The purpose of this research; was to investigate the academic self-efficacy of the university students studying in the field of sports according to various variables. The sample group of the study consisted of 386 (female, 42.7% male, 57.3%) volunteer university students who were educated in physical education and sports teaching, sports management and coaching education departments by convenience sampling method. In order to collect the necessary information, a personal information form was used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…Concerning gender, the results of this study demonstrated that no statistically significant differences were found between males' and females' self-efficacy and that the differences between the means were likely due to chance. This is consistent with the findings of Ngoc Truong and Wang (2019) and other studies (Azar, 2010;Clutts, 2010;Koçak & Canli, 2019;Vuong et al, 2010;Yoestara & Putri, 2019). However, although the differences between males' and females' self-efficacy beliefs were significant in favor of males in some studies (e.g.…”
Section: Research Question Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning gender, the results of this study demonstrated that no statistically significant differences were found between males' and females' self-efficacy and that the differences between the means were likely due to chance. This is consistent with the findings of Ngoc Truong and Wang (2019) and other studies (Azar, 2010;Clutts, 2010;Koçak & Canli, 2019;Vuong et al, 2010;Yoestara & Putri, 2019). However, although the differences between males' and females' self-efficacy beliefs were significant in favor of males in some studies (e.g.…”
Section: Research Question Onesupporting
confidence: 92%
“…In fact, more research is required about the impact of these circumstances on university students' self-efficacy. A recent unique study by Koçak and Canli (2019) investigated the self-efficacy beliefs of 386 university students studying sports according to the place they were raised. Their findings demonstrated that participants who were raised in a province or district reported higher self-efficacy beliefs than those who were raised in a village.…”
Section: Factors Affecting Students' Self-efficacy Beliefs In Moroccamentioning
confidence: 99%
“…In addition, this study found a difference between the self-efficacy levels of males and females in favour of females. This finding contradicts the previous studies which found no significant differences between males' and females' selfefficacy (e.g., Azar, 2010;Kahraman et al, 2014;Omari et al, 2020;Vuong et al, 2010;Koçak & Canli, 2019;Yoestara & Putri, 2019). Additionally, the found difference between the self-efficacy levels of males and females in this study was in favour of females, which is opposite of the findings of Vogt et al, (2007), Altunsoy et al, (2010), Diseth et al, (2014), which had found females had lower levels of self-efficacy than males.…”
Section: Discussioncontrasting
confidence: 99%
“…As a result, the present study investigated a category of individual differences, termed demographic factors, which are likely to affect the EFL learners' self-efficacy beliefs. Based on the results, like what Koçak and Canli (2019) concluded, "it can be said that the demographic variables are not an important factor in academic self-efficacy of the students" (p. 56). The results of this study hopefully could be insightful for the field of educational psychology because as Dinther et al (2011) argued that educational programs can improve learners' self-efficacy, "and that educational programmes based on social cognitive theory proved to be particularly successful on this score" (p. 95).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation